Discourse about the end of the world - Brzozowska, Dorota (Lingua Posnaniensis, 2014)
The increased prevalence of discourse concerning the expected end of the world was observed in various countries and manifested in various genres especially in the years 2000 and 2012. Some of the discourse was conducted in a serious manner, whereas other instances included humorous motifs and were used for commercial purposes. The aim of this paper is to take a closer look at the typical motifs prevailing in the discourse concerning the end of the world, with special emphasis on the humorous aspect – both universal and culturespecific. Texts found on Polish, German, English and Russian websites were analyzed. In the studied material, the end of the world was understood literally and broadly – in terms of extermination of the human race, eschatology – or narrowly, in terms of statistical data concerning the death of a given number of people, or even individually, referring to the imminent ending of each person’s particular world. The metaphorical meaning of the end of the world was also used in the sense of “a commotion”, “the pressure of business”, “a mess, confusion”, and “accumulation of problems”, referring mostly to the functioning of particular institutions or lack of access to the Internet, or reviving common stereotypes.